Kemampuan Siswa Kelas XI SMK PGRI 1 Tulungagung dalam Menemukan Konsep Barisan dan Deret - Maya Fidanata (Institut Agama Islam Negeri (IAIN) Tulungagung, 2018)
This study aims to describe the method of learning discovery learning with jigsaw type cooperative setting to improve student learning outcomes of sequence line and series XI SMK PGRI 1 Tulungagung. This type of research is a classroom action research. This research was conducted at SMK PGRI 1 Tulungagung in 2 stages, namely pre action and action stage. The action stage is implemented in 2 cycles and each cycle consists of 2 meetings. The results of this study can be concluded that the steps of learning mathematics that can improve student learning outcomes class XI APK-2 SMK PGRI 1 Tulungagung is preceded by apperception, the formation of groups of origin in heterogeneous, the formation of expert groups, the provision of stimuli or stimuli, students in groups identify problems, gather information, solve problems, verify, and conclude with the group. Furthermore, the students return to the origin group to convey to all members of the group of material origin that have been studied in the expert group in turn. Then the students presented the results of the discussion, held a quiz, award group and conducted a post test at the end of each meeting cycle. Student learning completeness of 95%, while the improvement of student's learning completeness of post test result of cycle I and post test result of cycle II equal to 37,5%.